Consorciação e plantas daninhas afetando a produtividade e a qualidade de sementes de sorgo - Nakagawa, Joao [UNESP] (2009)
This research aimed to study competition effects of legumes intercropping and weeds on seeds yield and quality of Sorghum bicolor (L.) Moench. The experiment was carried out in a Rhodic Nitisol, under field condition in Botucatu region, São Paulo State, Brazil. Ten treatments were tested: sorghum (cv. A-6304) intercropped with Dolichos lablab L., Mucuna aterrima (Piper et Tracy) Holland, Canavalia ensiformis D. C. or Crotalaria juncea L., that were sown in the same time of sorghum or 20 days after the sorghum sowing, and sorghum weed-free and sorghum without weeding. The experimental design employed was the completely randomized blocks with four replications. There were evaluated sorghum seeds yield and some characteristcs of seed quality: purity, hectolitric weight, 1000 seeds weight, insect infestation, germination and vigor (by first counting of germination test and accelerated ageing test). The competition caused by legumes intercropping and weeds affected the yield and the physical and physiological characteristics of sorghum seeds, but the intensity of prejudicial effects depended on the time and the species of legume intercropping.